Toxicity in the era of immune checkpoint inhibitor therapy - Keam, Synat; Turner, Naimah; Kugeratski, Fernanda G.; Rico, Rene; Colunga-Minutti, Jocelynn; Poojary, Rayansh; Alekseev, Sayan; Patel, Anisha B.; Li, Yuanteng Jeff; Sheshadri, Ajay; Loghin, Monica E.; Woodman, Karin; et al. (Frontiers in Immunology, 2024)
Immune checkpoint inhibitors (ICIs) reinvigorate anti-tumor immune responses by disrupting coinhibitory immune checkpoint molecules such as programmed cell death 1 (PD-1) and cytotoxic T lymphocyte antigen 4 (CTLA-4). Although ICIs have had unprecedented success and have become the standard of care for many cancers, they are often accompanied by off-target inflammation that can occur in any organ system. These immune related adverse events (irAEs) often require steroid use and/or cessation of ICI therapy, which can both lead to cancer progression.Although irAEs are common, the detailed molecular and immune mechanisms underlying their development are still elusive. To further our understanding of irAEs and develop effective treatment options, there is pressing need for preclinical models recapitulating the clinical settings.In this review, we describe current preclinical models and immune implications of ICI-induced skin toxicities, colitis, neurological and endocrine toxicities, pneumonitis, arthritis, and myocarditis along with their management.